Ambident reactivity of 5-aminopyrazoles towards donor–acceptor cyclopropanes. Issue 39 (23rd September 2022) - Vartanova, Anna E.; Levina, Irina I.; Ratmanova, Nina K.; Andreev, Ivan A.; Ivanova, Olga A.; Trushkov, Igor V.
Abstract : Donor–acceptor cyclopropanes were found to undergo ring opening with 5-aminopyrazoles via an attack by either an exocyclic amino group or a C(4) atom. Abstract : Lewis acid-catalysed reactions of donor–acceptor cyclopropanes with 1, 3-disubstituted 5-aminopyrazoles were investigated. Under catalysis with gallium(iii ) chloride, products of the three-membered ring opening via a nucleophilic attack of the exocyclic amino group were obtained in a chemoselective manner. Oppositely, in the presence of scandium(iii ) triflate, products of either N -alkylation or C (4)-alkylation, or a mixture of both were formed. The products of the C (4) alkylation were transformed in one step into tetrahydropyrazolo[3, 4- b ]azepines that are attractive for medicinal chemistry and pharmacology.